Geodynamics of the Caucasus – Anatolian-Arabian region and Turkey-Syria Earthquakes 2023 - Valentina, Svalova (Journal of Basic & Applied Sciences, 2023)
The activation of natural disasters in the world requires the development of new approaches to the study of geological processes, in particular, at the boundaries of lithospheric plates, characterized by earthquakes, increased seismicity, volcanism, landslide processes, tsunamis and other dangerous natural processes and hazards. Earthquake of M 7.8 struck south -eastern Turkey and north - western Syria on 6 February 2023. The M 7.8 earthquake is the largest in Turkey since the 1939 Erzincan earthquake, and the second-strongest recorded in the country, after the 1668 North Anatolia earthquake. More than 52,800 deaths were confirmed: more than 46,100 in Turkey, and more than 6,700 in Syria. It is the deadliest natural disaster in Turkey's modern history. The earthquakes caused over US$100 billion in damages. The geodynamic models construction for the deep structure of natural hazards regions is an important contribution to the study of active continental margins, which is necessary for the earthquake forecast, prediction and prognosis, assessing geoecological risks and preparing population actions in the event of natural disasters and catastrophes. The Caucasus - Arabian region is a complex highly-stressed geodynamic structure, characterized by increased heat flow, high seismicity, magmatism and volcanism. The geodynamics of the Caucasus - Arabian region is determined by the collision of the Eurasian and Arabian lithosphere plates, as well as the complex history of the development of the Alpine-Himalayan belt and surrounding territories. The problem solution of geological structures formation and evolution in various complex geodynamic settings and natural hazards forecast and prognosis requires an analysis of all available geological - geophysical data, as well as the formulation and solution of problems of mechanical and mathematical modeling. Slow lithospheric deformations are simulated by models of viscous flow in multi-layered, incompressible, high-viscosity Newtonian fluid, using Navier-Stocks equation and discontinuity equation. The solution of the inverse problem of geodynamics by the direct method is developed. The first inverse problem of geodynamics was solved - the restoration of the velocity fields, pressures and stresses at the depth of the lithosphere according to the available data on the velocities on the surface. The second inverse problem of geodynamics has been posed and solved - the determination of the movement of boundaries at the depth of the lithosphere based on the given movements of the surface. The solutions obtained can be used to analyze deep geodynamic problems, and together with geothermal modeling, geological and geophysical methods and seismic tomography can serve as a reliable apparatus for studying deep geodynamics due to the formation and evolution of geological structures and the lithosphere stress-strain state researches. The solution of the problem is analyzed on the example of the Caucasus - Arabian region geodynamics. The Geodynamic concept of geoenvironment has been developed. Geodynamic models of the regions of hazardous natural processes in order to predict and prevent natural disasters and catastrophes are constructed. An algorithm for creating monitoring systems is suggested.